Phase 2 Study of Bortezomib Combined With Temozolomide and Regional Radiation Therapy for Upfront Treatment of Patients With Newly Diagnosed Glioblastoma Multiforme: Safety and Efficacy Assessment - Kong, X.; Nguyen, N.; Choi, Y.; Zhang, Guicheng; Nguyen, H.; Filka, E.; Green, S.; Yong, W.; Liau, L.; Green, R.; Kaprealian, T.; Pope, W.; et al. (Elsevier Inc., 2018)
© 2018 Elsevier Inc. Purpose: To assess the safety and efficacy of upfront treatment using bortezomib combined with standard radiation therapy (RT) and temozolomide (TMZ), followed by adjuvant bortezomib and TMZ for =24 cycles, in patients with newly diagnosed glioblastoma multiforme (GBM). Methods and Materials: Twenty-four patients with newly diagnosed GBM were enrolled. The patients received standard external beam regional RT with concurrent TMZ beginning 3 to 6 weeks after surgery, followed by adjuvant TMZ and bortezomib for =24 cycles or until tumor progression. During RT, bortezomib was given at 1.3 mg/m2 on days 1, 4, 8, 11, 29, 32, 36, and 39. After RT, bortezomib was given at 1.3 mg/m2 on days 1, 4, 8, and 11 every 4 weeks. Results: No unexpected adverse events occurred from the addition of bortezomib. The efficacy analysis showed a median progression-free survival (PFS) of 6.2 months (95% confidence interval [CI] 3.7-8.8), with promising PFS rates at =18 months compared with historical norms (25.0% at 18 and 24 months; 16.7% at 30 months). In terms of overall survival (OS), the median OS was 19.1 months (95% CI 6.7-31.4), with improved OS rates at =12 months (87.5% at 12, 50.0% at 24, 34.1% at 36-60 months) compared with the historical norms. The median PFS was 24.7 months (95% CI 8.5-41.0) in 10 MGMT methylated and 5.1 months (95% CI 3.9-6.2) in 13 unmethylated patients. The estimated median OS was 61 months (95% CI upper bound not reached) in the methylated and 16.4 months (95% CI 11.8-21.0) in the unmethylated patients. Conclusions: The addition of bortezomib to current standard radiochemotherapy in newly diagnosed GBM patients was tolerable. The PFS and OS rates appeared promising, with more benefit to MGMT methylated patients. Further clinical investigation is warranted in a larger cohort of patients.